Integrating U-Th, 14C, and 210Pb methods to produce a chronologically reliable isotope record for the Belize River Valley Maya from a low-uranium stalagmite. (July 2019) - Akers, Pete D; Brook, George A; Railsback, L Bruce; Cherkinksy, Alex; Liang, Fuyuan; Ebert, Claire E; Hoggarth, Julie A; Awe, Jaime J; Cheng, Hai; Edwards, R Lawrence
Social and environmental changes had great spatiotemporal variability in the Maya Lowlands during the Classic and Postclassic Periods, and stalagmites promise high-resolution paleoclimate data that can refine our understanding of this complex time. Unfortunately, stalagmites in this region are often difficult to date by U-Th methods because of low initial uranium concentrations. Other dating techniques can be used on such stalagmites, and we present here an age–depth model for BZBT1, a low-uranium stalagmite sampled from Box Tunich cave in the Belize River Valley. This age–depth model dates the growth of BZBT1 to between 400 and 1610 yr BP (340–1550 CE) by combining evidence from U-Th results, radiocarbon dating of both stalagmite CaCO3 and trapped organic material, and 210 Pb dating. The resulting stable isotope record from BZBT1 reveals paleoclimate changes that affected local Maya populations during the Classic and early Postclassic Periods. This record is further refined by isotopically tuning the BZBT1 data with two other regional stalagmite records. Our work offers additional paleoclimate insight into the relationship between the Maya and their environment from a stalagmite that would typically be disregarded for research purposes. Continued research into alternative dating techniques for speleothems can enable additional scientific discovery while promoting speleothem conservation.